Managing care through the air [remote health monitoring]. - Ross, P.E.
This work describes the efforts of various companies to take advantage of wireless technology to develop devices that would allow remote monitoring of older people. The focus is on developing electronic devices to handle cognitive decline, cancer, cardiovascular and other aging-related diseases. The aim is to deduce the actions of older people in their homes through a network of wireless sensors and use that information to help patients comply with doctors' orders, enable remote caregiving by family and friends, and detect early signs of disease and prevent its progression.
Keywords: Battery-powered sensor; Motes; Neurological disorders diagnosis; Wireless network; Wireless remote monitoring; Wireless sensors